Israeli business in transition - Emily Udler (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
Despite the burden of an enormous defense budget, the absorption of immigrants, its tiny size and the scarcity of natural resources, Israel's economy, albeit with considerable financial aid from abroad, was able to achieve impressive growth rates. This was to a great degree accomplished by putting a heavy emphasis on education and by rapidly achieving a high degree of industrialization through government policies and incentives. But in recent years, with increasing government deregulation and enormously altered global power structures Israel is faced with a dynamic new reality. Israel's ability to continue or even heighten its growth rate will be very much dependent on the ability of the individual businesses to adapt and adjust rapidly to these new realities. This study of organizational learning in Israel was undertaken in order to understand what factors and mechanisms are involved in Israeli companies' ability or lack thereof to successfully cope with the challenges of this rapidly changing environment. Top executives representing more than 55% of the companies employing 500 workers or more, were interviewed. Two distinct patterns of learning, related to three basic elements, emerged from the data. These elements are the image of the individual employee, the organizational and decision-making structure of the company, and the specific corporate culture. Of particular interest in Israel is the significant number of companies which exhibit mixed features of these two learning patterns. In these “hybrid“ companies, which tend to have a history of centralized learning characteristics, there is a growing interest in the flexibility commonly associated with decentralization and the flattening of hierarchical pyramids of decision-making. The study also discusses factors that promote or hinder organizational learning such as crises and success. – – In den zurückliegenden Jahrzehnten hatte Israels Wirtschaft mit beträchtlicher finanzieller Unterstützung aus dem Ausland, einer starken Bildungsförderung sowie einer staatlichen Industriepolitik enorme Wachstumsraten erzielt. Seit den letzten 10-15 Jahren ist auch Israels Wirtschaft mit einer neuen weltpolitischen Situation und mit Deregulierungen im eigenen Wirtschaftssystem konfrontiert. Ob Israels wirtschaftliche Wachstumsraten der Vergangenheit erhöht oder auch nur gehalten werden können, wird stark von der Fähigkeit der einzelnen Unternehmen abhängen, sich an diese neuen Bedingungen anzupassen. Um die Lernfaktoren und Lernmechanismen in israelischen Unternehmen zu verstehen, wurden Topmanager in Firmen mit über 500 Beschäftigten befragt. Eine Analyse der Interviews ließ zwei charakteristische Lernmuster, nämlich das ,,zentralisierte“ und das ,,dezentralisierte“ Lernmuster, erkennbar werden. Diese Lernmuster definieren sich jeweils über drei charakteristische Elemente: die Ausprägung des Menschenbildes, die Ausprägung der Organisations- und Entscheidungsstruktur und die Ausprägung der Unternehmenskultur. Auffällig ist in Israel die beträchtliche Anzahl der Firmen, die Eigenschaften beider Lernformen in sich vereinen. Diese ,,hybriden“ Unternehmen haben in der Regel eine Vergangenheit, die vom ,,zentralisierten“ Lernmuster geprägt ist. Manager dieser Unternehmen äußern jedoch ein zunehmendes Interesse an einer Eigenschaften wie Flexibilität, die gewöhnlich mit Dezentralisierung und flachen Hierarchien in Unternehmen assoziiert wird. Im Rahmen dieser Studie werden auch lernförderliche und lernhinderliche Faktoren - wie etwa Krisen und Erfolg - diskutiert.
Keywords: 330; Reorganisation; Führungskräfte; Lernprozess; Wirtschaftliche Anpassung; Israel